Treatment of congenital adrenal hyperplasia in children aged 0-3 years: a retrospective multicenter analysis of salt supplementation, glucocorticoid and mineralocorticoid medication, growth and blood pressure - GÜRAN, TÜLAY (My University, 2022)
Objectives: International guidelines recommend additional salt supplementation during infancy in classic congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency. The influence of corticoid medication and growth has not been assessed. Aim: To investigate the current use of salt supplementation, fludrocortisone (FC) and hydrocortisone (HC) dosage as well as weight, height, BMI and blood pressure (BP) in CAH children aged 0–3 years. Methods: Retrospective multicentre analysis using data from the I-CAH registry. Salt-treated (ST) and non-salt-treated (NST) children were compared regarding FC and HC dosage, weight, height and BP at 0, 3, 6, 9, 12, 18, 24, 30, and 36 months. Results: We analysed 2483 visits of 331 patients born after year 2000 in 13 countries (male, n  = 145) with 203 ST patients (61%). NST children had significantly higher FC dosages at 1.5–4.5 months and higher HC dosages until 1.5 months of age. No differences in weight, length and BP between subgroups were observed. Children of the whole cohort showed increased BMI-SDS during the study period and about half of the reported BP readings were >P95. Conclusion: In children treated with additional salt supplementation, FC and HC dosages are lower during the first months of life but without differences in weight, length and BP until 3 years of age compared to NST children. All children showed an increase in BMI-SDS and a high rate of BP readings >P95 until 3 years, indicating the start of weight gain and negative effects on blood pressure already in very early life.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrinoloji; Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Yaşam Bilimleri; Endocrinology; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Life Sciences